Case report: Metastatic melanoma derived from a somatic-type malignant transformation of a mediastinal teratoma treated with immune checkpoint inhibitors - Rosenfeld, Roberto; Riondino, Silvia; Parisi, Giusy; Iannantuono, Giovanni Maria; Ajdhoni, Rexhina; Torino, Francesco; Mariotti, Sabrina; Roselli, Mario (Frontiers in Oncology, 2024)
The treatment of patients affected by a teratoma with somatic-type malignancy (STM) is challenging, since they are characterized by a poor prognosis, due to chemoresistance to standard cisplatin-based regimens. Only five more case reports were described for melanomatous STM and for which there are no data available for efficacy evidences of immune checkpoint inhibitors in this setting. Here we report the case of a patient with an initial diagnosis of mediastinal pure seminoma at the first biopsy. After four cycles of a standard cisplatin-based regimen and a partial response, a radical surgery was performed, revealing a mediastinal teratoma with triple STM component (melanoma, leiomyoarcoma and primitive neuroectodermal tumor). However, during post-surgical follow-up, he developed distant metastases from the melanomatous component and a first-line treatment with immune checkpoint inhibitors (ICI) was started.